IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR PADA MATA PELAJARAN PAI DAN BUDI PEKERTI DI SMPN KOTA BATAM - Ramadhan, Bagus Wahyudi; Rochbani, Ita Tryas Nur; Sumianti, Sumianti (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
The purpose of this study is to analyze the application of constructivism theory to Islamic Education teachers' strategies in instilling Islamic moral values at State Senior High School 35 in South Halmahera. The method used in this study is qualitative with a case study approach. Data were obtained through observation, interviews, and documentation, then tested for validity using triangulation techniques. PAI teachers play an important role as facilitators, mentors, and role models in the learning process. The strategies used include modeling, motivation, discussion, habituation, and worship practices. These strategies proved to be effective when integrated with Vygotsky's constructivism theory through the concepts of scaffolding and the zone of proximal development, as well as John Dewey's theory, which emphasizes experience-based and reflective learning. The application of constructivism theory in PAI learning can help make the learning process more contextual, interactive, and reflective so that students are able to implement Islamic moral values in their daily lives. Thus, PAI teachers need to continue to develop innovative learning strategies in order to shape a generation with Islamic morals.